The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jfd.13165
|View full text |Cite
|
Sign up to set email alerts
|

Review of diseases and health management in zebrafish Danio rerio (Hamilton 1822) in research facilities

Abstract: The use of zebrafish (Danio rerio) in biomedical research has expanded at a tremendous rate over the last two decades. Along with increases in laboratories using this model, we are discovering new and important diseases. We review here the important pathogens and diseases based on some 20 years of research and findings from our diagnostic service at the NIH-funded Zebrafish International Resource Center. Descriptions of the present status of biosecurity programmes and diagnostic and treatment approaches are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 98 publications
0
33
0
3
Order By: Relevance
“…Edwardsiella ictaluri , a Gram-negative bacteria, is a deadly pathogen in zebrafish ( Danio rerio ) ( 12 , 13 ). In the present study, we found that zebrafish Bid could induce apoptosis in piscine cells, similar to previous observations in mammals ( 1 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Edwardsiella ictaluri , a Gram-negative bacteria, is a deadly pathogen in zebrafish ( Danio rerio ) ( 12 , 13 ). In the present study, we found that zebrafish Bid could induce apoptosis in piscine cells, similar to previous observations in mammals ( 1 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we have been investigating the aetiology, pathogenesis, etc., of various zebrafish fish diseases for the last two decades. Two common intestinal diseases are epithelial carcinomas (Paquette et al., 2013; Spagnoli & Murray, 2020) and severe infections by the nematode Pseudocapillaria tomentosa (Kent & Sanders, 2020; Kent, Sanders, Spagnoli, Al‐Samarrie, & Murray, 2020). As part of the Zebrafish International Resource Center (ZIRC) diagnostic programme (http://zebrafish.org/health/index.php), we have examined many healthy and moribund zebrafish from over 300 facilities from 2000, and the worm and intestinal neoplasms (small cell carcinomas or adenocarcinomas) were observed in about 10% and 16% of the facilities, respectively (Kent et al, 2020).…”
Section: Worm Positive Worm Negative Row Totalsmentioning
confidence: 99%
“…Zebrafish and humans share more than 10,000 genes, accounting for approximately 70% of the human genome [ 31 ]. For this reason, many human drugs elicit similar physiological responses in zebrafish, making them a good model for toxicity assessments [ 32 ]. Additionally, low operation fee is another advantage, since zebrafish can reproduce a lot of offspring easily.…”
Section: Introductionmentioning
confidence: 99%